PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN PADA PT. ASKRINDO (PERSERO) - B31109112, Yuliansyah (Jurnal Manajemen Update, 2016)
This study aims to determine how the influence of motivation, organizational culture, and job satisfaction on organizational commitment of employees at PT Askrindo (Persero) Branch Pontianak. This research was conducted by the method of associative research can be constructed a theory that serves to explain, predict and control a phenomenon / phenomena. Collecting data using primary data obtained by distributing questionnaires to employees Askrindo PT (Persero) Branch Pontianak. The sample in this study using the census sampling, in which all members of the population used as a sample that as many as 21 people.The number of population and sample to be studied in PT. Askrindo (Persero) Branch Pontianak.Results from the study showed that work motivation significantly influence the organizational commitment at PT .Askrindo( Persero ) Branch of Pontianak , with a significance value of 0.000, which is smaller than α 0.05 . Organizational culture is no significant influence of organizational culture on organissionalcommitment , with a significance value of 0.869 greater than α 0,05.Kepuasan work significantly influence organizational commitment at PT . Askrindo( Persero ) Branch of Pontianak, with a significance value of 0.000, which is smaller than α 0.05 ..   Keywords:      Motivation, Organizational Culture and Job Satisfaction Organizational Commitment Against